Time-Varying Impact of Commodity Prices on Output Growth and Inflation in the Eastern European Countries - Roman Kopych; Viktor Shevchuk (Commodities, 2023)
Using quarterly data for the 2002–2022 period, we estimate the output and inflation effects of several commodity prices (agricultural raw materials, crude oil, and metals) for 8 Eastern European countries with different exchange rate regimes. The Kalman filter is used for estimating the time-varying parameters. Our main findings can be summarized in the following way: (i) higher crude oil prices are inflationary in most of the countries (except Slovakia), with a stronger price effect since 2020; (ii) crude oil prices are neutral with respect to output growth in 4 out of 8 countries, with an expansionary effect in Croatia, Slovenia, and Romania, as well as a contractionary effect in Slovakia, but the crude oil shock of 2021–2022 seems to be expansionary in almost all countries (except Slovakia), regardless of the exchange rate regime practiced; (iii) inflation and output effects of metals prices are quite heterogeneous across countries; (iv) agricultural raw material prices play a role in both inflation and output growth only in Bulgaria and Poland. Since 2021, a growing inflationary impact of crude oil prices suggests a stronger monetary policy reaction to the oil shock, especially in the presence of its favorable output effect.